Measurement of exposed carbon (II) oxide and air particulate matter concentrations in aba metropolis - Uche Stephen Akataobi (Wolters Kluwer Medknow Publications, 2019)
Purpose: This study measured the level of air pollution; carbon monoxide (CO) and air particulate matter caused by human activities in Aba metropolis. Ten sample locations were selected from the most busy and populated part of the city (Aba South), based on human activities such as burning of tires, wood, rubber materials, construction and factory activities, vehicular emission, and the use of combustion engines. Material and Methods: Level of pollution was measured in the ten sample locations using Gasman air monitor for CO and Haz-Dust monitor for perticulater matter; once a week, twice a month (the 1st and 4th week) for 4 months. Results: Data collected were analyzed using one-way analysis of variance; the highest mean average value of 66.81 ppm was recorded in Water Side Junction, 4.508 ppm in Asa/Azikiwe Junction, 42.506 and 42.166 ppm in Main Park and Ngwa Road Junction, 39.667 ppm in Opopo Junction, 36.009 ppm in Portharcut Road Junction, 35.833 in New Market Road Junction, 33.833 ppm in Milverton Junction, whereas 33.666 ppm in Bata Junction was recorded as the lowest mean value of CO. PPM gave an average mean value between 4.921 μg/m3 and 5.415 μg/m3. Conclusion: The result then indicates CO pollution in the sampled locations.